All‐in‐One, Wireless, Stretchable Hybrid Electronics for Smart, Connected, and Ambulatory Physiological Monitoring - Kim, Yun‐Soung; Mahmood, Musa; Lee, Yongkuk; Kim, Nam Kyun; Kwon, Shinjae; Herbert, Robert; Kim, Donghyun; Cho, Hee Cheol; Yeo, Woon‐Hong (Advanced science, 2019)
Commercially available health monitors rely on rigid electronic housing coupled with aggressive adhesives and conductive gels, causing discomfort and inducing skin damage. Also, research‐level skin‐wearable devices, while excelling in some aspects, fall short as concept‐only presentations due to the fundamental challenges of active wireless communication and integration as a single device platform. Here, an all‐in‐one, wireless, stretchable hybrid electronics with key capabilities for real‐time physiological monitoring, automatic detection of signal abnormality via deep‐learning, and a long‐range wireless connectivity (up to 15 m) is introduced. The strategic integration of thin‐film electronic layers with hyperelastic elastomers allows the overall device to adhere and deform naturally with the human body while maintaining the functionalities of the on‐board electronics. The stretchable electrodes with optimized structures for intimate skin contact are capable of generating clinical‐grade electrocardiograms and accurate analysis of heart and respiratory rates while the motion sensor assesses physical activities. Implementation of convolutional neural networks for real‐time physiological classifications demonstrates the feasibility of multifaceted analysis with a high clinical relevance. Finally, in vivo demonstrations with animals and human subjects in various scenarios reveal the versatility of the device as both a health monitor and a viable research tool. Continuous and ambulatory assessment of health conditions, such as cardiac abnormalities, heart and respiratory rates, and activity detection, is enabled by the development of a stretchable hybrid electronic platform based on thin‐film metals, miniature chip packages, and strategic integration of hyperelastic polymers, suggesting a new standard for multifunctional health monitoring in both clinical and research settings.